2018
DOI: 10.1101/288837
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Systematic studies of all PIH proteins in zebrafish reveal their distinct roles in axonemal dynein assembly

Abstract: Construction of motile cilia/flagella requires cytoplasmic preassembly of axonemal dyneins before transport into cilia. Axonemal dyneins have various subtypes, but the roles of each dynein subtype and their assembly processes remain elusive in vertebrates. The PIH protein family, consisting of four members, has been implicated in the assembly of different dynein subtypes, although evidence for this idea is sparse. Here, we established zebrafish mutants of all four PIH-protein genes: pih1d1, pih1d2, ktu, and tw… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 48 publications
4
24
0
Order By: Relevance
“…Mutations in DNAAF4/DYX1C/PF23 result in loss of the majority of IDAs and a fraction of ODA in Chlamydomonas flagella (Yamamoto et al, 2017). MOT48 functions in preassembly of IDAs and homologous to the protein interaction with Hsp90 1 (PIH1) domain-containing protein of the R2TP complex (Yamamoto et al, 2010; Yamaguchi et al, 2018). Chlamdyomonas RuvBL1 and RPAP3 are homologs of RuvBL1 and RPAP3 of the human R2TP complex, respectively (Maurizy et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mutations in DNAAF4/DYX1C/PF23 result in loss of the majority of IDAs and a fraction of ODA in Chlamydomonas flagella (Yamamoto et al, 2017). MOT48 functions in preassembly of IDAs and homologous to the protein interaction with Hsp90 1 (PIH1) domain-containing protein of the R2TP complex (Yamamoto et al, 2010; Yamaguchi et al, 2018). Chlamdyomonas RuvBL1 and RPAP3 are homologs of RuvBL1 and RPAP3 of the human R2TP complex, respectively (Maurizy et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…TWI1 is a homolog of PIH1D3, which is implicated dynein arm preassembly in mouse and zebrafish (Dong et al, 2014; Yamaguchi et al, 2018). Currently, it is not known whether TWI1 has a similar function in Chlamydomonas .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Scale bar: 10 nm. ( b ) Combined with genetic perturbation, subtomogram averaging defined the roles of individual dynein assembly factors in the organization of the zebrafish sperm axoneme [ 102 ]. ( c ) Three-dimensional segmentation unveiled the complex organization of the isolated bovine sperm connecting piece, revealing novel fibrous linkers between plates of the segmented columns [ 103 ].…”
Section: Cryo-electron Microscopy Is Poised To Make Important Contribmentioning
confidence: 99%
“…Cryo-ET also provides a means to assess the molecular effects of targeted genetic disruption. Studies in zebrafish revealed how mutations in different dynein assembly factors resulted in structural defects at specific positions in the axoneme ( figure 5 b ), which could be related to altered patterns of sperm motility [ 102 ]. Genetic perturbation can also have larger-scale effects on morphology, and the multi-scale capability of cryo-ET allows it to capture these as well.…”
Section: Cryo-electron Microscopy Is Poised To Make Important Contribmentioning
confidence: 99%